Elogio crítico ao princípio da Justiça Fiscal: uma abordagem a partir dos pressupostos da Teoria Sistêmica de Niklas Luhmann - Braga, Tiago Musser dos Santos (2020)
From predominantly philosophical and sociological considerations, it was concluded that justice in taxation is unlikely. The tax phenomenon does not include a balance between economic agents. This Summary begins with this pessimistic news from this Critical Praise to the Principle of Fiscal Justice. Although it seems daunting, this is a work that strives for optimism that is complacent with the reality of the world glimpsed by labor practice in taxation. It was not sought to analyze a certain legal system, making critical considerations. Instead. Through shared arguments from the Systems Theory thought by the German sociologist Niklas Luhmann, this Thesis has shown that Tax Justice is a contingency formula, which does not realize true justice because of the unlikelihood of Communication success, which acts directly on Trust. of the economic agents. Thus, this finding serves as a stimulus for the legal system itself to create mechanisms that minimize communication difficulties in the tax field, raising the confidence of individuals and favoring the socioeconomic development of societies around the world